Financial Performance of Islamic Versus Conventional Banks a Comparative Analysis for Jordan - Neifar, Malika; Charfeddine, Sameh; Kammoun, Aida (International Journal of Economics and Financial Issues, 2022)
This paper contributes to the empirical literature on interest-free finance by investigating the financial performance of interest-free and conventional banks in Jordan over the period 2005–2014 covering GFC period. Three models, two sub-periods, and 11 ratios are considered to compare bank performance evolutions. We give first a univariate based t-test analysis, and then a discriminant analysis is presented in order to determine which variables differentiate between conventional and Islamic banks. Finally, a multivariate nonlinear analysis from Binary outcome panel data models such as Probit and Logit model is conducted. Based on t-test univariate analysis, there is significant evidence that Islamic Banks (IBs) are in average less stable and more risky than conventional banks (CBs) for the three considered periods: full period, pre Global Financial Crisis(GFC) and post GFC. Pre GFC, IBs are more capitalized, more liquid, and more profitable in average. However, post GFC, IBs are in average only more liquid in addition to excess of instability and credit risk. From the results of Pooled Probit model, interest free banks seem again to be less stable, but less liquid, and riskier for the total period. The failure to find more stability for IBs is due to assumption of a stable relationships. Once we introduce interaction effect variables to take into account of behavior instability (due to Subprime crisis (GFC)), we show that IBs are rather more stable, more liquid but less profitable post GFC.